Terminological description of extremism in international acts and national criminal laws - Zhilina, Natalia Yu.; Lukyanchikova, Elena F.; Kovalenko, Dmitrij V.; Mironuk, Ivan V.; Prokhorova, Marina L. (Linguistics and Culture Review, 2021)
Based on a meaningful analysis of international legal act provisions and criminal legislation of foreign states, the article presents the approaches to the terminological characterization of the concept of "extremism" and its legislative regulation. The conclusion is made about the lack of a united strategy to the definition of the studied theory, which complicates international relations and collaboration in the realm of countering extremist crimes. A comparative analysis of the legislative regulation of extremist crimes in foreign countries allows us to identify common features and trends in the development of legal responsibility for extremism in foreign countries, to establish differences in the legal regulation of this problem, and to develop approaches to the unification of this concept at the level of international legislation.